A study on customers perception towards the merchandise offer at Orchard Square Shah Alam / Azlina Abdul Hamid - Abdul Hamid, Azlina (1997)
The purpose of the research is to get an opinion and views from the customers of Orchard Square Shah Alam whether they satisfied or not with the current merchandise being offered at the store. Instead of determining the customers perception, it also hoping that they will contribute some ideas and opinion towards improving the merchandise offer. It is important to maintain and improve the merchandise since it has major influence on customers to come to the store as well as making decision to buy. One more thing, a good merchandise offer may develop the customers satisfaction. The results of the survey showed that, majorities of the respondents were dissatisfied with the current merchandise being offered at the store. The dissatisfaction comes from both the varieties as well as the assortment of the merchandise. Most of them were always faced the experiences of understocking at Orchard Square Shah Alam, and these has been create a poor image on their minds. From the result of the survey, it can be concluded and recommended that the customers want Orchard Square Shah Alam to improve their merchandise offer in terms of its varieties, color, brand, size, style, and quality. It is important to be noted by the management in order to build a good relationship with the customers as well as meeting the customers needs and wants. The satisfaction of the customers may create a good perception and image of the organization.